The Concentration and Competition of Vietnam Mobile Telecommunications Market Through HHI and Elasticity of Demand 2 - Dang, Duc; Dang Thi Viet, Duc (VNU Journal of Science: Policy and Management Studies; Vol 33 No 2DO - 10.25073/2588-1116/vnupam.4087, 2017)
The article uses the Hirschman-Herfindahl Index (HHI) and the Elasticity of Demand to evaluate the degree of concentration and competition of Vietnam's mobile telecommunications market. For the HHI calculation, the article uses revenue market share data. For estimation of price elasticity of demand, the article uses a regression model with aggregate data of the whole market. The estimation results show high HHI, suggesting high concentration of the Vietnam mobile market which can harm the competition in the market. The high estimated price elasticity of demand indicates that price is actually powerful tool of competition in Vietnam. This gives implications for regulatory bodies for regulation options applied in the market. Key words: Market concentration, Price elasticity of demand, Competition, Mobile telecommunications market.